2022
DOI: 10.1007/s00404-022-06860-2
|View full text |Cite
|
Sign up to set email alerts
|

Fetal pancreas size and maternal serum biomarkers glycated albumin and insulin-regulated aminopeptidase provide no potential for early prediction of gestational diabetes mellitus

Abstract: Purpose We aimed to determine the predictive values of fetal pancreas size and maternal serum biomarkers glycated albumin (GA) and insulin-regulated aminopeptidase (IRAP) for gestational diabetes mellitus (GDM). Materials and methods In this prospective observational study including 109 pregnant women, the fetal pancreas size and maternal serum biomarkers GA and IRAP were measured at the gestational age of 20–22 weeks and later at the gestational age of 24–28 weeks, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Low levels of sIRAP expression at ~ 0.06 ng/ Vol:. ( 1234567890 www.nature.com/scientificreports/ ml and ~ 2 ng/ml were also reported in other studies in pregnant women between 20-22 and 25-35 weeks gestation, respectively 19,20 . However, since measurements in non-pregnant, healthy controls were missing in these studies and in all other studies examining circulating IRAP [21][22][23][24] , it is difficult to draw any conclusions on IRAP levels in healthy humans.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Low levels of sIRAP expression at ~ 0.06 ng/ Vol:. ( 1234567890 www.nature.com/scientificreports/ ml and ~ 2 ng/ml were also reported in other studies in pregnant women between 20-22 and 25-35 weeks gestation, respectively 19,20 . However, since measurements in non-pregnant, healthy controls were missing in these studies and in all other studies examining circulating IRAP [21][22][23][24] , it is difficult to draw any conclusions on IRAP levels in healthy humans.…”
Section: Discussionsupporting
confidence: 74%
“…In the study by Trocme, et al 17 , the reported size of the recombinant sIRAP bands in their Western blots does not correspond to the known size of sIRAP (~ 150 kDa), appearing instead at as a 180 kDa band which does not represent full-length (165 kDa) or dimerised (> 250 kDa) IRAP. In the few other reported studies measuring circulating IRAP as a biomarker for pre-diabetes 18 , gestational diabetes 19 , preeclampsia 20 and prostate cancer 21 , commercially available ELISA kits were used, but no information was provided for the ELISAs on the region of IRAP the antibodies are directed against or validation of their specificity.…”
Section: Discussionmentioning
confidence: 99%